Pendampingan Inovasi Teknologi Dalam Sistem Pembayaran di PT. Gecok Halal Indonesia - Naya, Candra; Fatchan, Muhamad; Permana, Indra; Fitriani (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
Assistance with technological innovation in payment systems at PT. Gecok Halal Indonesia" will discuss the approach and methodology used in developing technological innovation capabilities in the company. This training aims to increase employee understanding and skills in adopting and implementing the latest innovations in payment systems that comply with halal standards in Indonesia. The main focus of the training includes an in-depth understanding of modern payment technology, innovation implementation strategies, and compliance with applicable halal regulations. The methodology used includes interactive training sessions, case studies and group discussions to ensure comprehensive understanding as well as practical application in the workplace. It is hoped that this training will provide a significant boost in accelerating the adoption of technological innovation at PT. Gecok Halal Indonesia, so that companies can continue to compete in an increasingly complex market and meet consumer demands for security and reliability in technology-based payment systems.